REFERENCE FOR A PRELIMINARY RULING ON CJEU: THOUGHTS AND OBSERVATIONS IN CRIMINAL MATTERS - Liakopoulos, Dimitris (Revista de Estudos Jurídicos da UNESP, 2020)
Purpose of this investigation is to give answers and make a technical/procedural overview on preliminary reference in criminal matters as well as to examine the application of art. 267 TFEU in the context of criminal proceedings. Over the last eight years, therefore, the urgent preliminary ruling procedure, initially dictated by the material nature of dispute, has evolved into an institution closer to specific requirements of criminal procedural law, where the request for urgent procedure takes place based on person’s situation involved in the trial before the referring court. System rationale reflects the realization of an ever-increasing integration of EU law into national law, even in criminal matters which has always been reserved for the exclusive competence of states.